Factors Influencing Farmers' Land Function Transfer In Waiheru Village, Baguala District - Mutiara Farha Fathima; Jeter D. Siwalette; Marfin Lawalata (Cita konsultindo, 2024)
Waiheru Village is one of the central locations for vegetable production in Baguala District, which is located not far from the city center and is busy cultivating several types of vegetables, including chilies, tomatoes, kale, long beans, spinach, mustard greens and eggplant. In reality, the vegetables being cultivated have been going well because farmers can produce vegetables in large quantities at each production time, but farmers in Waiheru Village have several limitations in terms of production factors such as land ownership (not their own and relatively small). In Waiheru Village, during the period from 2021 to 2022, the total area of farmers' land has decreased by around 5 ha, namely from 25 ha to 20 ha. In Waiheru Village there are 15 farmer groups consisting of 10 vegetable farmer groups and 5 food farmer groups. Every month each farmer group is able to produce 12-13 tonnes of leaf vegetable crops, while for fruit vegetable crops they are able to produce 5-6 tonnes every 2 months, for food crops such as cassava each year they are able to produce 30-40 tonnes at harvest time.